2017
DOI: 10.1021/acs.iecr.7b03521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Ion in Bulk VPO in Aldol Condensation of Formaldehyde and Methyl Acetate to Methyl Acrylate

Abstract: The metal ion effect on the bulk VPO was investigated using the aldol condensation of methyl acetate and formaldehyde to methyl acrylate. The VPO catalyst with 2 mol % Zr exhibited the highest methyl acrylate formation rate of 18.6 μmol·g–1·min–1. A combination of X-ray diffraction, BET, TPD, XPS, and EPR, together with activity testing data, was utilized to analyze and explain the origin of the metal ion effects. The promotion of methyl acrylate production by the intercalation of Zr was associated with its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…As shown in Fig. 5, the NH 3 desorption peaks over 5%-VPO/MCF and 33%-VPO/MCF emerges at 150–275 °C, suggesting the presence of weak acid sites on the MCF supported VPO catalysts 29 . On the unsupported VPO, the NH 3 desorption peaks appear at 150–300 °C and 350–450 °C, indicating the existence of weak and medium strong acid sites.…”
Section: Resultsmentioning
confidence: 88%
“…As shown in Fig. 5, the NH 3 desorption peaks over 5%-VPO/MCF and 33%-VPO/MCF emerges at 150–275 °C, suggesting the presence of weak acid sites on the MCF supported VPO catalysts 29 . On the unsupported VPO, the NH 3 desorption peaks appear at 150–300 °C and 350–450 °C, indicating the existence of weak and medium strong acid sites.…”
Section: Resultsmentioning
confidence: 88%
“…22 Ji and co-workers 16 studied a series of multiphase VPO catalysts by varying the preparation and activation conditions and observed that the δ-VOPO 4 was a key component for the reaction. Li and co-workers 23 prepared a series of metal cation-doped VPO catalysts and found that a VPO catalyst doped with 2% Zr showed the highest activity. Zhu and co-workers 3 reported that the Nb doping could modify the catalyst surface acidic property and the oxidation state of V atoms, and enhance the catalyst activity accordingly.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Acetic acid is commercially produced on a large scale and begins with methanol and CO. Formaldehyde is produced as a by‐product in many chemical processes. A significant amount of research has been conducted on the synthesis of acrylic acid (or methyl acrylate) via the aldol condensation reaction of acetic acid (or methyl acetate) with formaldehyde catalyzed by alkaline metals and V‐P‐O oxides . When the Cs/SBA‐15 catalyzed the aldol condensation reaction between the methyl acetate and the formaldehyde, the methyl acrylate selectivity was able to reach 95 % at a methyl acetate conversion of 48.4 % .…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that the β‐VOPO 4 , δ‐VOPO 4 , and distorted (VO) 2 P 2 O 7 phases played important roles in the formation of acrylic acid and methyl acrylate . The addition of alkaline metals in the V‐P‐O oxide catalysts caused the formation of phosphate salts and changed their alkaline and acidic properties, subsequently improving their catalytic performance in the formation of acrylic acid …”
Section: Introductionmentioning
confidence: 99%